Handke’s Kaspar, Wittgenstein’s Tractatus, and the successful representation of alienation - Hamilton, James R. (Journal of Dramatic Theory and Criticism, 1995)
Handke’s Kaspar, Wittgenstein’s Tractatus, and the successful representation of alienation